Medical emergencies in dental practice: A nationwide web-based survey of Italian dentists. Issue 3 (March 2023) - Varoni, Elena M.; Rigoni, Marta; Lodi, Giovanni; Sardella, Andrea; Muti, Paola; Vitello, Antonio; Montebugnoli, Lucio; Polimeni, Antonella; Tommasino, Stella; Iriti, Marcello; Senna, Andrea; Iandolo, Raffaele; et al.
Abstract: Objective: Dentists must be prepared to manage medical emergencies, which are arisen during dental practice together with the increase of age population and medically compromised patients. This study aims at assessing the occurrence of medical emergencies in a cohort of Italian dentists, to ascertain their level of confidence in the management of these conditions, also based on their educational training and type of medical graduation, and, finally, to know their educational needs, in order to plan appropriate institutional interventions for specific training. Methods: A national-based cross-sectional study was carried out by means of an online survey sent to all dentists working in Italy. Results: The survey included 6818 questionnaires. Most of the respondents (n = 4443; 65.2%) reported the occurrence of at least one medical emergency during their professional life. The events rarely resulted in death as declared by only 62 (0.9%) of respondents. The commonest medical emergency was the vasovagal syndrome. Most medical emergencies occurred during the dental procedure (n = 4883; 71.6%). An average degree of satisfaction about the ability to diagnose and manage medical emergencies was reported by most of respondents, with high level of confidence in treating vasovagal syndrome, while a lack in preparedness about the management of myocardial infarction or transient ischemic attack (TIA) and stroke. Medical doctors were more confident in managing the emergencies than dentistry graduates (p < .01). Considering the educational needs, almost all of participants (n = 6721; 98.6%) declared the need to improve their training and expressed their interest in theoretical-practical institutional courses as well as in the establishment of an official national register for medical emergencies occurred in dental practice. Conclusions: Medical emergencies are not negligible and the dentist should receive adequate training and continuing education to be updated and ready for their correct management. Clinical significance: The dentist should be ready to deal with medical emergencies and provide first aid to the patient. The dentist is not always prepared to manage the most complex emergencies; therefore, there is the need to organize post-graduate courses and to set up an emergency register. Highlights: Medical emergencies are not rare events during dentist's professional life. Medical emergencies in the dental setting rarely result in patient's hospitalization or death. The commonest medical emergency is the vasovagal syndrome. Updates in the medical emergency management remain an urgent need for dentists.